INSTITUTIONALIZATION OF THE PARTY SYSTEM IN THE REPUBLIC OF KAZAKHSTAN: AST AND PRESENT - KARMAZINA, Lidia (CENTRAL ASIA AND THE CAUCASUS, 2008)
Political pluralism and a multi-party system are regarded today not only as the basic principles of a democratic society, but also as the fundamental prerequisites of democracy in general. In this context, Kazakhstan, which declares itself to be a democratic state,1 has been giving much attention recently to transforming the country’s political sphere. A retrospective view of the development of a multi-party system in the republic makes it easier to break down the institutionalization of its party system into relatively distinct stages. During the first stage (1985-August 1990), the state’s ideology crumbled and fell apart, the multiparty system became legitimized, and the people experienced euphoria over the imminent changes. “Politics was regarded as a process during which vitally important issues were indeed resolved, and this atmosphere gave rise to an outburst of public enthusiasm and drew charismatic personalities onto the political stage.”2 Numerous independent public associations with views on society and the state that differed from the official stance began to spring up. In so doing, organizations prevailed that did not pursue political goals but were engaged in social problems—environmental, culturological, and historical—and tried to have an influence on the power structures in order to resolve these problems. The most well-known of them were: the Nevada-Semipalatinsk International Anti-Nuclear Movement (Nevada-Semipalatinsk IAM, date of establishment—February 1989), the Memorial Society (December 1988), Adilet (April 1989) and Multi-thousand meetings and other mass actions were held under the supervision of well-known poet O. Suleimenov, thus helping Nevada-Semipalatinsk IAM to achieve its goal: the Semipalatinsk testing ground in Kazakhstan was closed down. This experience stood the movement leaders in good stead. They were later able to create a political organization on its basis. The Memorial and Adilet societies were engaged in investigating the Stalinist repressions, helping the victims to become rehabilitated, and looking for mass shooting and burial sites. The Republican Society set itself the task of reviving the Kazakh language, culture, and spirituality; its national-cultural centers strove to preserve the national cultures of the various ethnic groups living in Kazakhstan